An atomistic insight into light‐sensitive polymers with methylstilbene building blocks. Issue 7 (29th January 2015) - Bandeira, Nuno A. G.; Tylkowski, Bartosz; Bogdanowicz, Krzysztof Artur; Giamberini, Marta; Bo, Carles
<x xml:space="preserve">Abstract</x> The work reported elucidates some of the structural and optical features of methylstilbene‐based microcapsules by means of quantum chemical calculations.